Prevalence of skin wounds in working donkeys in Bukombe, Tanzania. (7th March 2020) - Rayner, Emma; Airikkala‐Otter, Ilona; Susheelan, Aswin; Gibson, Andrew; Itaba, Richard; Mayani, Thomas; Mellanby, Richard J; Gamble, Luke
Abstract : Background: Preventable wounds are a common welfare issue in working donkeys in many countries. In the Bukombe District of Tanzania, there are estimated to be 3000 working donkeys, used primarily to transport loads for direct income generation. For historical reasons, oxen‐yoke carts are used; their design is inappropriate for donkeys and results in serious neck wounds. The project aim was to assess the prevalence and nature of wounds in working donkeys. Methods: In November 2018, 148 donkeys owned by 48 owners were examined, and data were collected. Results: The study revealed that one or more wounds were present in 56.1% of the population and yoke‐related, dorsal neck wounds comprised 79.5% of these. These wounds ranged in surface area from 1 cm 2 to 300 cm 2 . Clinically, 96.6% of all wound types were superficial and the majority of these (51.1%) were granulating. Conclusion: These data will enable the future evaluation of targeted interventions aimed at reducing the prevalence of these specific wounds.